The Anticariogenic Effect of Sugar-Free Gum Containing CPP-ACP Nanocomplexes on Approximal Caries Determined Using Digital Bitewing Radiography - Morgan, M.V.; Adams, G.G.; Bailey, D.L.; Tsao, C.E.; Fischman, S.L.; Reynolds, E.C. (Caries research, 2008)
This study investigated, using digital bitewing radiography, the progression and regression of approximal caries in adolescent subjects chewing a sugar-free gum containing 54 mg CPP-ACP relative to the identical gum without CPP-ACP. 2,720 subjects from 29 schools were randomly assigned to one of the two gums and were instructed to chew their assigned gum for 3 × 10 min/day, with one session supervised on school days, over the 24-month study period. Standardized digital bitewing radiographs were taken at the baseline and 24-month clinical examinations for each subject. The radiographs, scored by a single examiner, were assessed for approximal surface dental caries at both the enamel and dentine level. Surface level transitions were scored using a transition matrix. Caries progression or regression was analysed using proportional-odds ordered logistic regression modelling of the transition scores at the tooth surface level. There was a statistically significant difference in the frequency distributions of the transition scores between the two gum groups (OR = 0.82, p = 0.03). For subjects chewing the CPP-ACP gum the odds of a surface experiencing caries progression were 18% less than those of a surface experiencing caries progression for subjects chewing the control gum. In conclusion, the 54 mg CPP-ACP sugar-free gum significantly slowed progression and enhanced regression of approximal caries relative to a control sugar-free gum in a 24-month clinical trial.